Hybridization Of Gold Fish (Carassius Auratus Auratus) With Nilem (Osteochillus Hasselti) - Yandra, Eka; Alawi, Hamdan; ', Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from February-June 2014 in Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The objective of this research was to evaluate the intergeneric hybridization between gold fish (Carassius auratus auratus) with silver sherkminow fish (Osteochillus hasselti) by comparing the fertilization rate, hatching rate, survival rate in four days (SR-4), survival rate for 30 days (SR-30), extra weight and value heterosis ( hybrid vigor ) between fish larvae results hybridization with fish control. The method is applicable in the experimental methods, where spawning artificial was conducted by the use of eggs and fish sperm of a comet (Carassius auratus auratus) and fish nilem (Osteochillus hasselti) that has been injected using ovaprim with a dose of 0,5ml / kg.The highest percentage of fertilization is marriage ♂ K x ♀ K (75.04%), follow by ♀ K x ♂ N (70.87%), ♀ N x ♂ N (31.3%) ♀ N x ♂ K 30.14%. Persenatage the highest hatching is a control that is ♂ K x ♀ K (91.50%), which followed ♀ N x ♂ K (88.37%), ♀ N x ♂ N (87.44%) and ♀ K x ♂ N (68.67%). The highest percentage of survival rate 30 days in sequence is ♀ K x ♂ K (69.08%), ♀ N x ♂ N (60.17%) and ♀ K x ♂ N (2.06%). As for hybrid ♀ N x ♂ K died at the age of 4 and 5 days. The highest weight added sequentially is the larvae of spawning results ♀ K x ♂ N (0,23 g), ♀ K x ♂ K (0,21 g) dan ♀ N x ♂ N (0,19 g). All values of heterosis is negative except at the FR (33.29 %) and extra weight (15.25 %) from ♀ K x ♂ N.Key words : hibrydization, gold fish, nilem